The Correlation Analysis for New Media Internet Celebrity Economy in College Students’ Entrepreneurial Values and Entrepreneurial Behavior - Xiang, Yonghui; Wang, Weiwei (Frontiers in Psychology, 2022)
Driven by the development of new media, the Internet celebrity economic marketing model has gradually become one of the mainstream online marketing models. It has aroused warm attention on the network platform and provided a breakthrough for entrepreneurship for college students. This thesis aims to explore the influence of the Internet celebrity economy on college students' entrepreneurial values and entrepreneurial behavior. A questionnaire is conducted among students in two colleges in Xi'an. Moreover, a theoretical model is constructed according to the influence principle of entrepreneurial values on entrepreneurial behavior. The reliability and validity of the questionnaire data are analysed, and the mediating and moderating effects are tested. The questionnaire results show that contemporary college students generally focus on Internet celebrity mainly through the live broadcasting platform and shopping platform, among which entertainment and shopping account for the largest proportion. More than 40% of college students are optimistic about the impact of the Internet celebrity economy and remain rational and objective on the whole. The model analysis results suggest that entrepreneurial values directly positively and significantly affect the entrepreneurial behavior. The entrepreneurial intention has an incomplete mediating effect in the influence mechanism of the Internet celebrity economy on entrepreneurial behavior. The chain double mediating composed of entrepreneurial motivation and entrepreneurial intention has an incomplete mediating effect in the indirect impact of the Internet celebrity economy on entrepreneurial behavior. Entrepreneurial policy satisfaction has a moderating effect on the impact path of entrepreneurial intention on the entrepreneurial behavior. The research results can guide college students to view the Internet celebrity economy rationally and objectively. Combined with the school's entrepreneurship education curriculum, the results have a certain reference significance for shaping college students' entrepreneurial values and guiding their entrepreneurial behavior.